STRATEGI PENGELOLAAN DAN PROMOSI MUSEUM (OBJEK STUDI : MUSEUM SENI RUPA DAN KERAMIK, KELURAHAN PINANGSIA, KECAMATAN TAMAN SARI, JAKARTA BARAT) - Christine Atania; Parino Rahardjo; B.Irwan Wipranata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Apart from being a tourist attraction, museums also have a function as a place for us as a society to learn and get to know about history. So that the museum has an important role in society. Lack of museum management has made public interest in the museum lessened. People generally visit museums with the aim of being curious and wanting to get benefits. However, in reality the management of this museum cannot meet the needs of the community, and makes the museum unable to carry out its role as a public and social facility in providing services to the community. The purpose of this writing is to determine the performance of museum management, to determine the weaknesses of the museum, and to make a management strategy proposal for the Museum of Fine Arts and Ceramics to increase public interest. The author examines the existing literature in relation to management, promotion, and museums. The data used consisted of primary data (the existing condition of the museum, interviews, and questionnaires) and secondary data consisting of MSRK documentation, comparative museum documentation, and others. By using five analysis tools and five analysis methods. To find out how the management strategy can be applied, the writer uses analysis (location, physical condition of the museum, management performance, best practices, and perceptions and preferences). The results of the author's research are in the form of strategic proposals for the management and promotion of the Fine Arts and Ceramics Museum. Keywords:  Management; Museum of Fine Arts and Ceramics; PromotionAbstrakMuseum selain sebagai objek wisata juga memiliki fungsi sebagai tempat kita sebagai masyarakat belajar dan mengenal tentang sejarah. Sehingga museum memiliki peran penting dalam masyarakat. Kurangnya pengelolaan museum membuat ketertarikan masyarakat pada museum berkurang. Masyarakat pada umumnya berkunjung ke museum memiliki tujuan dari rasa keingintahuan dan ingin mendapatkan manfaat. Namun pada kenyataan pengelolaan museum ini tidak dapat memenuhi kebutuhan masyarakat, serta membuat museum tidak dapat melaksanakan peran sebagai fasilitas umum dan sosial dalam memberi pelayanan kepada masyarakat. Tujuan penulisan tersebut ialah mengetahui kinerja pengelolaan museum, mengetahui faktor kelemahan museum, dan membuat usulan strategi pengelolaan untuk Museum Seni Rupa dan Keramik guna meningkatkan minat masyarakat. Penulis mengkaji literatur yang ada berkolerasi dengan pengelolaan, promosi, dan museum. Data yang digunakan terdiri dari data primer (kondisi eksisting museum, wawancara, dan kuesioner) serta data sekunder yang terdiri dari dokumentasi MSRK, dokumentasi museum pembanding, dan lainnya. Dengan menggunakan lima alat analisis dan lima metode analisis. Untuk mengetahui bagaimana strategi pengelolaan dapat diterapkan penulis menggunakan analisis (lokasi, kondisi fisik museum, kinerja pengelolaan, best practices, serta persepsi dan preferensi). Hasil penelitian penulis yaitu berupa usulan strategi terhadap kegiatan pengelolaan dan promosi Museum Seni Rupa dan Keramik.